CSC264 - Introduction To Web And Mobile Application / College of Computing, Informatics And Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2022)
The course introduces the students to web programming. It covers, among others, mark-up language, client-side scripting, and server-side scripting.